In vitro metabolism of lidocaine in subcellular post-mitochondrial fractions and precision cut slices from cattle liver. (October 2021) - Punt, Ans; Lautz, Leonie; Stoopen, Geert; Pinckaers, Nicole; Rijkers, Deborah; Essers, Martien; Hoogenboom, Ron
Abstract: In vitro models are widely used to study the biotransformation of xenobiotics and to provide input parameters to physiologically based kinetic models required to predict the kinetic behavior in vivo . For farm animals this is not common practice yet. The use of slaughterhouse-derived tissue material may provide opportunities to study biotransformation reactions in farm animals. The goal of the present study was to explore the potential of slaughterhouse-derived bovine liver S9 (S9) and precision cut liver slices (PCLSs) to capture observed biotransformation reactions of lidocaine in cows. The in vitro data obtained with both S9 and PCLSs confirm in vivo findings that 2, 6-dimethylaniline (DMA) is an important metabolite of lidocaine in cows, being for both PCLSs and S9 the end-product. In case of S9, also conversion of lidocaine to lidocaine-N-oxide and monoethylglycinexylidine (MEXG) was observed. MEGX is considered as intermediate for DMA formation, given that this metabolite was metabolized to DMA by both PLCSs and S9. In contrast to in vivo, no in vitro conversion of DMA to 4-OH-DMA was observed. Further work is needed to explain this lack of conversion and to further evaluate the use of slaughterhouse-derived tissue materials to predict the biotransformation of xenobiotics in farm animals. Highlights: Biotransformation of lidocaine in bovine liver S9 and precision cut liver slices In vitro and in vivo lidocaine mainly transformed into DMA Missing in vitro conversion of DMA into 4-OH-DMA Results can be used in kinetic model development to predict transfer to milk